2015
DOI: 10.1007/s00125-015-3513-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulin pump risks and benefits: a clinical appraisal of pump safety standards, adverse event reporting and research needs. A Joint Statement of the European Association for the Study of Diabetes and the American Diabetes Association Diabetes Technology Working Group

Abstract: Insulin pump therapy, also known as continuous subcutaneous insulin infusion (CSII), is an important and evolving form of insulin delivery, which is mainly used for people with type 1 diabetes. However, even with modern insulin pumps, errors of insulin infusion can occur due to pump failure, insulin infusion set (IIS) blockage, infusion site problems, insulin stability issues, user error or a combination of these. Users are therefore exposed to significant and potentially fatal hazards: interruption of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 20 publications
0
86
0
10
Order By: Relevance
“…As we move forward, it is important for professionals and patients to have a thorough understanding of insulin pump-associated adverse events in all their forms, and more research is needed to fully understand this aspect of CSII therapy. In addition, as recently recommended [48], pre-and post-marketing surveillance for adverse events should be transparent, appropriately categorised, and promoted for both manufacturers and consumers.…”
Section: Discussionmentioning
confidence: 98%
“…As we move forward, it is important for professionals and patients to have a thorough understanding of insulin pump-associated adverse events in all their forms, and more research is needed to fully understand this aspect of CSII therapy. In addition, as recently recommended [48], pre-and post-marketing surveillance for adverse events should be transparent, appropriately categorised, and promoted for both manufacturers and consumers.…”
Section: Discussionmentioning
confidence: 98%
“…In practice, our own attempts to analyze the FDA database (the EU database is not openly accessible) showed that the data stored represent a meaningless mess. 11 What is the reason for skin reactions, especially for contact dermatitis? Detailed information about adhesives is not readily available, especially regarding which materials are used in them.…”
mentioning
confidence: 99%
“…Although both CSII and MDI therapy are recommended treatment strategy for type 1 diabetic patients [9], CSII is more effective than MDI in reducing glucose variability [10,11]. Furthermore, a recent joint statement by ADA and EASD Diabetes Technology Working group [30] calls for an appropriate selection of candidates for pump therapy. As a corollary, the willingness to use an insulin pump by a Endocrine potential candidate is a necessary prerequisite.…”
Section: Discussionmentioning
confidence: 99%